The Public Purchases in Romania, A Geopolitical Dynamic of Yesterday and Today Environment - NUTA, Cristian Ionut (Annals of Spiru Haret University. Economic Series, 2017)
This paper intends to briefly explain how the internal regulations have changed lately concerning the Romanian Public Purchases.